MEASUREMENT OF THE MATURITY OF THE SOFTWARE REQUIREMENTS CHANGE MANAGEMENT PROCESS - Bhatti, M. W.; Manarvi, I. A. (The Nucleus, 2011)
In this paper, an extensive analysis is performed to develop a research instrument to measure the maturity of the software requirements change management process. The items of the research instrument are extracted from the existing literature of the software requirements change management process. A pilot study was conducted on small sample size (46 responses) for basic analysis of the data. After pilot study, a comprehensive analysis is performed on the large sample (162 responses) of data. In detailed analysis, the reliability analysis of the instrument is performed by computing the value of the cronbachâ€™s alpha. The content validity of the instrument is performed by a comprehensive review of the existing literature, by discussion of the items with the domain experts, by conducting a pilot study and by taking feedback from the professionals of the industry. The construct validity of the instrument is analyzed by the correlation matrix of the items, the value of the determinant, KMO and Bartlett's Test, total variance through eigenvalues, scree plot and component matrix. The criterion validity analysis of the instrument is computed by measuring the correlation, adjusted R-square and F-value with the â€œorganizational performanceâ€. The results of the analysis show that the selected items form a reliable and valid instrument for the measurement of the maturity of the software requirements change management process.